2003
DOI: 10.1074/jbc.m208974200
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin Stimulation of Vascular Adhesion Molecule-1 in Endothelial Cells Is Mediated by Protein Kinase C (PKC)-δ-NF-κB and PKC-ζ-GATA Signaling Pathways

Abstract: We recently demonstrated that thrombin induces the expression of vascular adhesion molecule-1 (VCAM-1) in endothelial cells by an NF-B-and GATA-dependent mechanism. In the present study, we describe the signaling pathways that mediate this response. Thrombin stimulation of the VCAM-1 gene and promoter in human umbilical vein endothelial cells was inhibited by preincubation with the phosphatidylinositol 3-kinase inhibitor, LY294002, the protein kinase C (PKC)-␦ inhibitor, rottlerin, a PKC-peptide inhibitor, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 65 publications
(57 reference statements)
4
88
0
Order By: Relevance
“…4,21 In accordance with data showing that PKC-d can activate NF-kB in several cell types, 22,23 we found that NF-kB is also a conduit for PKC-d in B-CLL cells (unpublished data). This prompted us to investigate whether higher constitutive expression levels of NF-kB in ZAP-70-expressing cells could explain the stronger apoptotic response after rottlerin treatment.…”
Section: Rottlerin Induces Apoptosis In Cll Cells I Ringshausen Et Alsupporting
confidence: 74%
“…4,21 In accordance with data showing that PKC-d can activate NF-kB in several cell types, 22,23 we found that NF-kB is also a conduit for PKC-d in B-CLL cells (unpublished data). This prompted us to investigate whether higher constitutive expression levels of NF-kB in ZAP-70-expressing cells could explain the stronger apoptotic response after rottlerin treatment.…”
Section: Rottlerin Induces Apoptosis In Cll Cells I Ringshausen Et Alsupporting
confidence: 74%
“…For instance, insulin-like growth factor-1, low density lipoprotein, VEGF, TNF-␣, and thrombin have each been shown to induce GATA2 activity at a posttranscriptional level without significantly changing GATA2 mRNA levels (14,46,47), whereas estrogen and transforming growth factor-␤ inhibit GATA2 binding (48,49). In contrast to GATA2, we have shown that inflammatory agonists such as TNF-␣ and thrombin down-regulate GATA3 expression at an mRNA level.…”
Section: Discussionmentioning
confidence: 44%
“…Indeed, GATA2 has been implicated in the regulation of a number of endotheliumspecific genes, including prepro-endothelin (9), endothelial nitric-oxide synthase (10), von Willebrand factor (11), intercellular adhesion molecule-2 (12), Down syndrome critical region-1 (13), and vascular endothelial cell adhesion molecule (VCAM) 3 -1 (14). The functional role, if any, for other GATA factors in endothelial cells has remained largely elusive.…”
mentioning
confidence: 99%
“…However, in thrombin-mediated ICAM-1 gene expression, transactivation of NF-B is dependent on the PKC␦/p38 MAPK pathway (29). A similar regulation by p38 MAPK in thrombin-induced NF-B stimulation and VCAM-1 (vascular cell adhesion molecule-1) expression was observed in human umbilical vein endothelial cells (43). Alternatively, PKC␦ may directly phosphorylate NF-B, resulting in enhanced DNA binding and transcriptional activity.…”
Section: Discussionmentioning
confidence: 92%